Answered

Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

f(x) = x³ - 3x² + 3x - 1

f(x + 1) What is the value?

A) x³+1

B) x³-1
C) x³
D) x²
E) x²+1


Sagot :

f(x)=(x-1)³ = x³ -3x² +3x -1 
f(x+1) = (x+1-1)³ = x³

[tex]f(x+1)=(x+1)^3-3(x+1)^2+3(x+1)-1\\ f(x+1)=x^3+3x^2+3x+1-3(x^2+2x+1)+3x+3-1\\ f(x+1)=x^3+3x^2+6x+3-3x^2-6x-3\\ f(x+1)=x^3 \Rightarrow C[/tex]